2019
DOI: 10.1103/physrevmaterials.3.024201
|View full text |Cite
|
Sign up to set email alerts
|

Electronically enhanced layer buckling and Au-Au dimerization in epitaxial LaAuSb films

Abstract: We report the molecular beam epitaxial growth, structure, and electronic measurements of singlecrystalline LaAuSb films on Al2O3 (0001) substrates. LaAuSb belongs to a broad family of hexagonal ABC intermetallics in which the magnitude and sign of layer buckling have strong effects on properties, e.g., predicted hyperferroelecticity, polar metallicity, and Weyl and Dirac states. Scanning transmission electron microscopy reveals highly buckled planes of Au-Sb atoms, with strong interlayer Au-Au interactions and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Other structural variants include Jahn-Teller driven cubic to tetragonal distortions, variations in the atomic site ordering (e.g. "inverse Heusler," D0 3 , and B2 cubic variants), and polar vs antipolar layer buckling patterns in the hexagonal variants [67,69,70].…”
Section: Quantum Materials Minus the Oxygenmentioning
confidence: 99%
See 3 more Smart Citations
“…Other structural variants include Jahn-Teller driven cubic to tetragonal distortions, variations in the atomic site ordering (e.g. "inverse Heusler," D0 3 , and B2 cubic variants), and polar vs antipolar layer buckling patterns in the hexagonal variants [67,69,70].…”
Section: Quantum Materials Minus the Oxygenmentioning
confidence: 99%
“…A significant challenge is that only a small subset of hexagonal Heuslers is natively insulating -an assumed requirement for switching via applied electric fields [105]. Epitaxial strain, quantum confinement, and Peierls-like distortions [67,70,106] may provide routes for tuning the buckling and opening a gap in polar compounds that are natively metallic.…”
Section: Opportunities At Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, while the intrinsic carrier concentration of silicon is n i ∼ 10 10 cm −3 at room temperature, typical experimental carrier concentrations for semiconducting half Heuslers are typically ∼ 10 19 to 10 21 cm −3 due to defects and nonstoichiometry, which are difficult to control to better than 1% [21]. In select cases it has been shown that several Sb-containing Heuslersincluding CoTiSb [22,23], NiMnSb [24,25], LuPtSb [26], LaPtSb [27], and LaAuSb [28] -can be grown with an excess Sb flux, in which the ratio of Sb to (X + Y ) is self-limiting. Since the stoichiometry of one out of three elements is self-limiting, this can be called semi adsorption control.…”
mentioning
confidence: 99%